The Effect of Product Attributes on Purchasing Decision for Palm Oil Derivatives (Case study: Chocolate Appolo at Bina Swalayan Medan) - Tambunan, Beryanto; Pinem, Laura Juita (Talenta Publisher, 2020)
The objective of this study is to analyze the effects of product quality, price, brand image and packaging can affect the purchasing decision for palm oil derivatives. This study conducted on the consumers of Bina Swalayan in Jalan Setia Budi Medan City. This study uses a primary source taken from 100 respondents by answering questionnaire. The result of this study determines that purchasing decision for palm oil derivatives is affected positively and significantly by product quality, price, brand image and packaging. The result of this study determine that the coefficient of determination (R-Square) obtained of 0,528, thus it can be determined that effect of product quality, product quality, price, brand image and packaging on purchasing decision for palm oil derivatives 52.8%, while remaining 47.2% is influenced by other factors. Keyword(s): Product Quality, Brand Image, Packaging and Purchasing Decision.